The Association of Combined GSTM1 and CYP2C9 Genotype Status with the Occurrence of Hemorrhagic Cystitis in Pediatric Patients Receiving Myeloablative Conditioning Regimen Prior to Allogeneic Hematopoietic Stem Cell Transplantation - Uppugunduri, Chakradhara Rao S.; Storelli, Flavia; Mlakar, Vid; Huezo-Diaz Curtis, Patricia; Rezgui, Aziz; Théorêt, Yves; Marino, Denis; Doffey-Lazeyras, Fabienne; Chalandon, Yves; Bader, Peter; Daali, Youssef; Bittencourt, Henrique; et al. (Frontiers in Pharmacology, 2017)
Hemorrhagic cystitis (HC) is one of the complications of busulfan-cyclophosphamide (BU-CY) conditioning regimen during allogeneic hematopoietic stem cell transplantation (HSCT) in children. Identifying children at high risk of developing HC in a HSCT setting could facilitate the evaluation and implementation of effective prophylactic measures. In this retrospective analysis genotyping of selected candidate gene variants was performed in 72 children and plasma Sulfolane (Su, water soluble metabolite of BU) levels were measured in 39 children following treatment with BU-CY regimen. The cytotoxic effects of Su and acrolein (Ac, water soluble metabolite of CY) were tested on human urothelial cells (HUC). The effect of Su was also tested on cytochrome P 450 (CYP) function in HepaRG hepatic cells. Cumulative incidences of HC before day 30 post HSCT were estimated using Kaplan-Meier curves and log-rank test was used to compare the difference between groups in a univariate analysis. Multivariate Cox regression was used to estimate hazard ratios with 95% confidence intervals (CI). Multivariate analysis included co-variables that were significantly associated with HC in a univariate analysis. Cumulative incidence of HC was 15.3 %. In the univariate analysis, HC incidence was significantly (p<0.05) higher in children older than 10 years (28.6 vs 6.8%) or in children with higher Su levels (>40 vs <11%) or in carriers of both functional GSTM1 and CYP2C9 (33.4 vs 4.2 %) compared to the other group. In a multivariate analysis, combined GSTM1 and CYP2C9 genotype status was associated with HC occurrence with a hazards ratio of 4.8 (95% CI: 1.3-18.4; p=0.02). Ac was found to be toxic to HUC cells at lower concentrations (33 µM), Su was not toxic to HUC cells at concentrations below 1 mM and did not affect CYP function in HepaRG cells. Our observations suggest that pre-emptive genotyping of CYP2C9 and GSTM1 may aid in selection of more effective prophylaxis to reduce HC development in pediatric patients undergoing allogeneic HSCT.